OPTIMASI KONSENTRASI AIR KELAPA DAN EKSTRAK LIDAH BUAYA UNTUK PERTUMBUHAN SETEK JAMBU AIR var. Citra (Syzygium aqueum) - Yahya, Muhammad Zaky; Susiyanti, Susiyanti; Yenny, Ratna Fitry; Laila, Alfu (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This research aimed to evaluate the effects of organic material concentrations and soaking durations on the growth of var. Citra water apple (Syzygium aqueum) stem cuttings. The experiment was conducted using a factorial Randomized Block Design with two factors: organic material concentration Z1 (100% coconut water), Z2 (10% aloe vera extract), and Z3 (100% coconut water + 10% aloe vera extract), as well as soaking durations P1 (8 hours), P2 (10 hours), and P3 (12 hours). These factors produced 9 treatment combinations, each repeated 3 times, resulting in 27 experimental units. Observed parameters included sprout emergence time, number of sprouts, sprout height, number of leaves, number of roots, root length, and survival rate. The research indicate that the combination of young coconut water and aloe vera extract (Z3) significantly influenced the number of leaves at 4 Weeks After Planting (WAP), with an average of 11,44 leaves. The soaking duration had a significant effect on sprouting time, with the 8-hour soaking treatment (P1) resulting in the earliest sprouting at an average of 7,16 days. Additionally, the number of shoots at 3, 4, and 5 WAP in the P1 treatment had average heights of 9,94 cm, 10 cm, and 8,33 cm, respectively. The number of leaves at 4 WAP in the P1 treatment averaged 11,55, while the number of roots at the end of the study averaged 10,83 in the P1 treatment. Keywords: Stem cuttings, Var. Citra, water apple, coconut water, aloe vera, growth regulators, soaking duration.